Syphilis Seropositivity in Blood Donors: A study at Multan - Saadia Latif, Hamid Iqbal, Jawad Zafar Chaudry, Taimoor Chughtai, Saadat Parveen, Aayza Mujahid, (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To determine syphilis seropositivity in healthy blood donors. Study design: Cross sectional analytical study Place and duration of study: Conducted atNishtar Medical Universityfrom February 2022 to July 2022. Methodology: Healthy blood donors of either gender between 18-50 years of age were included in study. All individuals were screened for transfusion transmissible infections including Syphilis. Data was collected by using preformed questionnaire that included information regardingsocio-demographic profile. The data was entered and analyzed by SPSS version 22.0. Results: Mean age of donors was 26.48±6.25 years. The highest proportion of donors was between 18-29 years age (69.2%). Majority (99.2%) blood donors were male. The marital status of the blood donors showed that 595 (81.9%) were single. The educational level of the participants revealed that about two third 465 (64.1%) blood donors had up to matric education and majority of blood donors 493 (67.9%) were resident of urban areas. The seropositivity of syphilis among donors was02.5%. The seropositivity of the syphilis is significantly associated with age (p<0.001), gender (p=0.001), educational level (p=0.001) and residence (p=0.05) of donors. Conclusion: Blood supply safety is dependent on screening of blood donors for transfusion transmissible infections. Therefore it must be compulsory to screen apparently healthy blood donors for syphilis. Keywords:Transfusion, Infection, Blood bank, Blood donors